LEGITIMIZING ELECTRONIC SCHOLARLY PUBLICATIONS: A DISCURSIVE PROPOSAL - Heimpel, Rod (Surfaces, 1999)
An electronic publication of scholarly work is not merely a paper publication in disguise. Legitimizing electronic scholarly publications calls for a new understanding of institutional underpinnings of the scholar’s world. Despite the fact that webpages are merely copies requested manually, by clicking on a mouse, they are conceived in spatial terms. Community is a logical metaphor for this space. Insistance on the idea of specialized virtual communities involves questions for the whole of the university institution.